Abundance of volatile organic compounds in white ash phloem and emerald ash borer larval frass does not attract Tetrastichus planipennisi in a Y‐tube olfactometer. (3rd June 2015) - Chen, Yigen; Ulyshen, Michael D.; Poland, Therese M.
Abstract: Many natural enemies employ plant‐ and/or herbivore‐derived signals for host/prey location. The larval parasitoid Tetrastichus planipennisi Yang (Hymenoptera: Eulophidae) is 1 of 3 biocontrol agents currently being released in an effort to control the emerald ash borer (EAB), Agrilus planipennis Fairmaire (Coloeptera: Burprestidae) in North America. To enhance its efficiency, allelochemicals that attract it need to be assessed. In this study, ash phloem volatile organic compounds (VOCs) of black, green, and white ash, and EAB larval frass were compared. Foraging behavior of T. planipennisi females in response to VOCs of white ash or frass from EAB larvae feeding on white ash phloem was tested using a Y‐tube olfactometer. Results indicated that the 3 ash species had similar VOC profiles. EAB larval frass generally contained greater levels of VOCs than phloem. Factor analysis indicated that the 11 VOCs could be broadly divided into 2 groups, with α ‐bisabolol, β ‐caryophyllene, ( E )‐2‐hexenal, ( Z )‐3‐hexenal, limonene, methyl benzoate, methyl indole‐3‐acetic acid, methyl jasmonate, methyl salicylate as the first group and the rest (i.e., methyl linoleate and methyl linolenate) as a second. Abundance of VOCs in white ash phloem tissue and frass, nevertheless, did not attract T. planipennisi females. The concealed feeding of EAB larvae might explain the selection for detectable and reliable virbrational signals, instead of undetectable and relatively unreliable VOC cues from phloem and frass, in short‐range foraging by T. planipennisi . Alternatively, it is possible that T. planipennisi is not amenable to the Y‐tube olfactometer assay employed.